Direct reading thinking activity and students’ reading comprehension: An experimental research - Diah Purwandari (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
The aim of this research is to find out the role of DRTA and Reading Attitude in improving students’ reading comprehension. Quasi-experimental design was used to establish the effect of method and attitude on students’ reading comprehension. Four classes of management were selected ,and assigned as experimental and control group, The experimental group were taught using DRTA and control classes were taught using regular method. ANOVA was used to examine the influence of the main effects and interaction effects of method and attitude on students’ reading comprehension. The result indicated that there was a significant difference effect between DRTA and Regular Method on students’ reading comprehension. DRTA was more effective in improving reading comprehension. There was, however, no significant difference in students' reading comprehension based on their attitude. This study also found a significant difference effect on students' reading comprehension based on the interaction between method and attitude. DRTA method was to be effective in students with low attitude, while the high attitude was more prone to conventional method.